Non-invasive monitoring of alternative splicing outcomes to identify candidate therapies for myotonic dystrophy type 1 - Ningyan Hu (Nature Portfolio, 2018)
Myotonic dystrophy type 1 (DM1) is associated with aberrant transcript splicing. Here, the authors develop a transgenic mouse model expressing a bi-chromatic reporter system that allows non-invasive monitoring of splicing of a transcript altered in DM1 in vivo, and show that it allows for evaluation of the therapeutic response to treatment with antisense oligonucleotides.